Flow Experience as a Mediator between Antecedents and Extra-Role Performance among Hotel Employees in Sarawak, alaysia - Kasa, Mark; Hassan, Zaiton; Ng, Jackelyn (International Journal of Engineering and Technology, 2018)
Employees who go beyond their job description are regarded as highly prized employees by organizations. This extra-role performance is often seen as a key indicator of whether employees are performing well in their job. Past studies linked engagement to be positively related to job performance, yet there are a limited number of studies on flow and performance, particularly on extra-role performance. This study was conducted on 290 hotel employees in Kuching, Sarawak, Malaysia to examine the correlation between flow experience and extra-role performance. In addition, this study also looked into flow as the mediator between the antecedents (job demand and job resources) and extra-role performance. The study hypothesized that flow experience is instrumental in employees’ extra-role performance. The results of the study suggested that flow correlated with the employees’ directional behaviour at work and flow mediates the correlation between job resources and extra-role performance. It was also discovered that flow did not mediate the correlation between job demand and extra-role performance. The findings indicated the benefits and practicality of flow experience on the employees’ extra-role performance and also the pros of retrospective flow experience.